2002
DOI: 10.1126/science.1065173
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase Recruitment and DNA Hypermethylation of Target Promoters by an Oncogenic Transcription Factor

Abstract: DNA methylation of tumor suppressor genes is a frequent mechanism of transcriptional silencing in cancer. The molecular mechanisms underlying the specificity of methylation are unknown. We report here that the leukemia-promoting PML-RAR fusion protein induces gene hypermethylation and silencing by recruiting DNA methyltransferases to target promoters and that hypermethylation contributes to its leukemogenic potential. Retinoic acid treatment induces promoter demethylation, gene reexpression, and reversion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
550
5
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 746 publications
(581 citation statements)
references
References 23 publications
16
550
5
4
Order By: Relevance
“…A few genetic mutations involving RARa were indeed reported in cancer cells and found associated with either RARb2 or Cyp26a1 downregulation. PML-RARa, an oncogenic protein associated with acute promyelocitic leukemia, which leads to block of myeloid maturation both in vitro and in vivo (He et al, 1998;Grignani et al, 2000), was shown to induce epigenetic repression of RARb2 in the presence of DNA methylation (Di Croce et al, 2002). However, we show that in embryocarcinoma cells RARb2 silencing can occur also by virtue of an accumulation of repressive Cyp26a1 is epigenetically regulated by retinoic acid receptors S Pozzi et al chromatin changes in the absence of DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…A few genetic mutations involving RARa were indeed reported in cancer cells and found associated with either RARb2 or Cyp26a1 downregulation. PML-RARa, an oncogenic protein associated with acute promyelocitic leukemia, which leads to block of myeloid maturation both in vitro and in vivo (He et al, 1998;Grignani et al, 2000), was shown to induce epigenetic repression of RARb2 in the presence of DNA methylation (Di Croce et al, 2002). However, we show that in embryocarcinoma cells RARb2 silencing can occur also by virtue of an accumulation of repressive Cyp26a1 is epigenetically regulated by retinoic acid receptors S Pozzi et al chromatin changes in the absence of DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of RAS [MacLeod et al, 1995], down regulation of Rb [Slack et al, 1999], or upregulation of the Wnt signaling pathway [Campbell and Szyf, 2003] leads to increased expression of DNMT1. Certain oncogenes could target DNMT to tumor suppressor genes and thus bring about regional hypermethylation [Fuks et al, 2001;Di Croce et al, 2002;Brenner et al, 2005;Vire et al, 2006]. An interesting possibility is that aberrant DNA methylation of cancer related genes could also come about through activation of signaling pathway by different environmental exposures, which might also include social exposures.…”
Section: Epigenetic Plasticity and Late Onset Pathologymentioning
confidence: 99%
“…After induction with 100 mM Zn for 12 h, cells were treated with 1 ng/ml 1a,25-dihydroxyvitamin D 3 for another 36 h. Cells were then analysed for CD14 expression by flow cytometry as described (Di Croce et al, 2002).…”
Section: Analysis Of Cell Differentiationmentioning
confidence: 99%